IMPLEMENTASI METODE WEB ENGINEERING DALAM MEMBANGUN SISTEM E-RESERVATION PEMESANAN KAMAR HOTEL - Helda Yudiastuti; Irwansyah Irwansyah (Jurnal Ilmiah Matrik, 2019)
This research was conducted at Hotel Telaga Biru Pagaralam, aims to create a new system that can overcome the problems that occur in the Hotel, especially in terms of booking rooms. The current room booking system is still done manually, which is still recorded in the book when guests check in until check out, then it is given a receipt as proof of payment in advance to the guest according to the length of the guest staying. In addition to coming directly customers can book a room by contacting the hotel by phone. For this, researchers are doing the action of making a system engineering information-based hotel reservation with the system development strategy using the Web engineering method, the tools used in the design are Unified Modelling Language (UML), in the development of this application authors use the PHP and MySql programming language as the Database of room booking systems. This system generates a system that allows customers and hotel to make bookings.